Demographic characteristics of complainers and non-complainers: a study on Malaysian mobile phone services industry’s consumers - A. Rahman, Mohd. Khirzan Badzli; Haron, Sharifah Azizah; Paim, Laily; Osman, Syuhaily; Wee, Hassnah (2016)
This study revealed the results of the demographic variables for complainer and non-complainer in mobile phone services industry. A total of 285 complainers and 230 non-complainers of mobile phone users in Selangor, Wilayah Persekutuan Kuala Lumpur and Putrajaya were selected as respondents by using mall-intercept approach. This descriptive study used frequency and percentage to show the results. The results were used in profiling the complainer and non-complainer. The mixed results showed that complainers were found using the post-paid plan, married, working in the public or private sector, and high monthly usage. Oher demographic variables such as gender, age, monthly income, ethnicity and financier for monthly bill payment the results were similar for both groups.